TS Gene Polymorphisms Are Not Good Markers of Response to 5-FU Therapy in Stage III Colon Cancer Patients - A. Fariña-Sarasqueta; M. J. E. M. Gosens; E. Moerland; I. van Lijnschoten; V. E. P. P. Lemmens; G. D. Slooter; H. J. T. Rutten; A. J. C. van den Brule (Analytical Cellular Pathology)
Aim: Although the predictive and prognostic value of thymidylate synthase (TS) expression and gene polymorphism in colon cancer has been widely studied, the results are inconclusive probably because of methodological differences. With this study, we aimed to elucidate the role of TS gene polymorphisms genotyping in therapy response in stage III colon carcinoma patients treated with 5-FU adjuvant chemotherapy.